1976
DOI: 10.1152/ajplegacy.1976.231.3.865
|View full text |Cite
|
Sign up to set email alerts
|

Duodenal and ileal adaptation to dietary calcium restriction: in vivo studies in the rat

Abstract: Intestinal adaptation by the growing rat to a low-calcium diet was studied by in situ perfusion of duodenum and ileum in vivo. Rats were fed diets containing either 1.2 or 0.02% Ca for 17-24 days. To study plasma-to-lumen flux and net calcium absorption, rats were loaded parenterally with 45Ca and perfused intraluminally with 3.4 mM calcium. Calcium restriction caused net absorption in ileum to increase fourfold, in duodenum almost twofold. With calcium restriction, plasma-to-lumen flux decreased in duodenum b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
9
0

Year Published

1978
1978
2008
2008

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(12 citation statements)
references
References 0 publications
3
9
0
Order By: Relevance
“…Some studies have shown a balance between true absorption and calcium secretion in the caecum (Petith and Schedl, 1976 ;Harrison and Harrison, 1969 ;Favus et al, 1980 ;Favus, Kathpalia and Coe, 1981 ;Lee et al, 1980). The present study agrees with the results of Cramer (1951) who reported significant phosphorus absorption in the terminal intestine of CV rats.…”
Section: Introductionsupporting
confidence: 93%
“…Some studies have shown a balance between true absorption and calcium secretion in the caecum (Petith and Schedl, 1976 ;Harrison and Harrison, 1969 ;Favus et al, 1980 ;Favus, Kathpalia and Coe, 1981 ;Lee et al, 1980). The present study agrees with the results of Cramer (1951) who reported significant phosphorus absorption in the terminal intestine of CV rats.…”
Section: Introductionsupporting
confidence: 93%
“…In the rat, absorption of calcium is more rapid at the duodenum than at the ileum both in vitro (15,16) and in vivo (3,17,18) and is composed of saturable and unsaturable components. Since the concentration of calcium in the luminal solution in the present study was 0.9mM, which is lower than the plasma ionized calcium concentration (1.25mM), calcium absorption across the gut wall was mainly by active transport.…”
Section: Discussionmentioning
confidence: 99%
“…We previously demonstrated that resec tion of the mid-small intestine of the rat pro duced markedly abnormal calcium transport responses by the residual duodenum and ileum [1], In normal rats, we found that both the cecum and colon responded to calcium depletion by increasing the net calcium ab sorption, suggesting a role for the large intes tine in calcium homeostasis [8] with extensive resection of the small intes tine, calcium absorption was significantly higher when the colon was preserved as com pared with ileostomy [5]. It was concluded that the colon is important in the absorption of calcium after small intestinal resection.…”
mentioning
confidence: 92%